Effectiveness Effectiveness of Wearable Electronic Device for Fall Risk Prevention in Community Elderly: A Literature Review - Cahyani, Kadek Dewi; Sukihananto; Astuti Yuni Nursasi (STIKes Al-Ma'arif Baturaja, 2024)
The increasing incidence of falls in the elderly has become a global health issue. The development of wearable electronic device technology is able to monitor daily activities, measure step counts, physical activity levels, and even sleep patterns of the elderly, while providing early warnings when changes occur that may increase the risk of falls. The aim is to see the effectiveness of using wearable electronic devices in preventing the risk of falls in the elderly in the community. PICO in this study is Population: Community-dwelling elderly, Intervention: wearable electronic device, Comparisons: none, and Outcome: fall prevention. Researchers used 3 search data sources, namely Embase, Pubmed, and Science Direct. The inclusion and exclusion criteria of this study are literature published in electronic data sources from 2018-2023, is a type of quantitative research, the elderly population in the community, English language and available in full text. This literature review includes ten articles that discuss the utilization of wearable electronic device technology, the types of wearable devices used include Inertial Measurement Units (IMU), biosensors, and accelerometers to evaluate the mobility, gait, and balance of the elderly. This literature review shows that wearable electronic device technology can effectively detect falls and motorize the incidence of falls in the elderly